A Framework for the Analysis of UAV Strategies Using Co-simulation - Barros, José de Sousa; Oliveira, Thyago; Nigam, Vivek; Brito, Alisson V. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2016: Anais do VI Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2016)
Systems using Unmanned Aerial Vehicles (UAV) are typical examples of cyber-physical systems. Designing such systems is not a trivial task because it brings the challenge of dealing with the uncertainty that is inherent to this type of system. Therefore, it is necessary the usage of appropriate tools for design that can ensure implementation of these systems with a certain level of confiability. Thus, the purpose of this work is to integrate two simulators via HLA in order to simulate and evaluate different flights strategies. For this, it is presented a simulation environment that can execute flight plans in order to evaluate different strategies in uncertain scenarios. The simulator was developed in Ptolemy and integrated with SITL/ArduPilot via HLA. With the use of the approach presented in this paper it is possible to obtain results closer to reality, thus more efficient flight strategies can be developed and evaluate.